Porous Ceramics: The Role of Coffee Grounds and Rice Husk Ash in Physical and Mechanical Properties - Fauzi; Evi Yufita; Endi Suhendi; Elin Yusibani; Afwandi Taga S; Rinaldi Romar; Musvira; Dini Rizqi Dwi Kunti Siregar (Universitas Negeri Surabaya, 2025)
This research investigates the role of spent coffee grounds (SCGs) and rice husk ash (RHA) as additives in clay mixtures for the production of porous ceramics. Three sample variations were tested. The first involved mixing SCGs with clay in weight percentages of 0:100, 5:95, 10:90, 15:85 and 20:80 %wt, using particles sized between 80 and 100 mesh. In the second variation, SCGs were replaced with RHA in similar proportions. The third variation used a fixed 10%wt SCG content, combined with varying RHA percentages (0, 5, 10, 15 and 20)%wt. Physical properties (density, porosity, water absorption) and mechanical properties (compressive strength) were evaluated. The results show that increasing the proportion of organic filler significantly decreases both density and compressive strength—by up to 45% and 97%, respectively—due to the reduced clay content. Conversely, porosity and water content increase with higher filler content. Among all samples, the clay–RHA mixture exhibited the highest compressive strength. Meanwhile, the combination of SCGs with 10%RHA produced ceramics with the lowest density, indicating the most porous structure.